Hospital outcomes of acute COVID-19 infection among patients with neurological conditions: a single-center study - Desouky, Adam; Fuentes, Venessa; Tiwari, Chhitij; Usui, Hikari; Smith Ayala, Arthor H.; Wilson, Susan E.; Diaz, Monica M. (Frontiers in Neurology, 2024)
Background Coronavirus disease 2019 (COVID-19) infection has been associated with severe neurological consequences, including stroke or seizures, and less severe neurological sequelae, including headaches, dizziness, and anosmia. Earlier COVID-19 variants were associated with high morbidity and mortality; however, knowledge of the impact of neurological conditions in the setting of COVID-19 on healthcare outcomes is limited. We sought to determine the impact of acute neurological conditions and acute COVID-19 infection on inpatient hospitalization outcomes. Methods This was a retrospective, observational study of adult patients who were admitted to a large academic medical center in the Southeastern US between April 2020 and December 2021 with acute COVID-19 infection and a neurological diagnosis. Patient demographics, medical history, neurological diagnoses, and hospitalization outcomes were obtained from the medical record. Descriptive statistics and unadjusted and adjusted logistic regression analyses were performed. Results Of the 1,387 patients included in this study, 27% died and 23% were kept under ventilation during hospitalization. The mean +/− standard deviation (SD) age was 64.6+/−16.9 years, with 52.8% women and 30.1% identifying as Black/African American. The most common neurological conditions included ischemic stroke (35.0%), movement disorder (12.0%), and hemorrhagic stroke (10.7%). In-hospital death was most common among those with epilepsy (p = 0.024), headache (p = 0.026), and dementia (p < 0.0001) compared to individuals without those conditions. Ventilation support was given more commonly to dementia patients (p = 0.020). Age was a significant risk factor for death (p < 0.001) and hospital length of stay (LOS) for ventilation (p < 0.001), but no neurological condition was a significant factor in adjusted logistic regression analyses. Discussion Mortality was high in this study, with more than one-quarter of patients dying in the hospital. Death was the most common among those with epilepsy, headache, or dementia, but no neurological condition increased the risk of in-hospital mortality or ventilation. Future studies would determine the long-term neurological sequelae of those discharged from the hospital with COVID-19 and a neurological condition.